Be very afraid of Kanako Inuki! - Inuki, Kanako (Kodansha USA Publishing, 2022)
"The six hair-raising stories selected for this collection feature an array of unnerving characters and scenarios brought to life in Inuki's signature art style, in the tradition of Junji Ito, Kazuo Umezu, Shintaro Kago, and Junko Mizuno."--Publisher.